Research on a New Mode of Oral English Teaching Based on Computer Network Assistance - Liu Yajie (MATEC Web of Conferences, 2022)
Oral English teaching is an important form of cultivating students' English accomplishment and improving their English learning effect. In the context of intelligent education, by giving full play to the advantages of computer network and actively reconstructing the new mode of Oral English teaching, we will, on the basis of optimizing the form of oral English teaching and by integrating high-quality oral English teaching resources, to promote students to participate in oral English learning and speaking practice in a conscious and spontaneous way. Based on the analysis of the existing problems in spoken English teaching, this paper puts forward the construction and implementation of a new spoken English teaching model based on computer network.